German pet owners advised to take precautions after cat dies of bird flu - Harding, Luke; Boseley, Sarah (2006)
German officials warned cat owners yesterday not to sleep accompanied by their pets, and to keep them indoors, following confirmation that a cat has died of the H5N1 avian flu virus. The cat was found at the weekend on the Baltic island of Rügen, near to where most of Germany's 121 cases of H5N1-infected wild birds have been found. Tests carried out on the animal by scientists at Germany's Friedrich-Loeffler institute confirmed H5N1, probably from having eaten infected birds.